Aktywność fizyczna studentów kierunku wychowania fizycznego w kontekście deklarowanych zachowań zdrowotnych = Physical activity undertaken by physical education students in the context of declared health behaviors - Guła-Kubiszewska, Halina; Dębska, Urszula; Starościak, Wojciech; Kałwa, Małgorzata; Hes, Bartłomiej (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Healthy, fit, and satisfied with life youth is the goal underlying all undertaken individual and social activities related to prevention and health actions. For this purpose, it is necessary to diagnose and monitor the condition of particular social and age groups. Accordingly, the authors decided to examine students of selected majors.
Keywords: aktywność fizyczna; zachowania zdrowotne; międzynarodowy kwestionariusz aktywności fizycznej; inwentarz zachowań zdrowotnych; physical activity; health behavior; International Physical Activity Questionnaire (IPAQ); Health Behavior Inventory (HBI)